2022
DOI: 10.3390/nu14071511
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Human Serum Metabolites Derived from the Intake of a Saffron Extract (Safr’InsideTM) Protect Neurons from Oxidative Stress: Consideration for Depressive Disorders

Abstract: Increases in oxidative stress have been reported to play a central role in the vulnerability to depression, and antidepressant drugs may reduce increased oxidative stress in patients. Among the plants exerting anti-inflammatory and anti-oxidant properties, saffron, a spice derived from the flower of Crocus sativus, is also known for its positive effects on depression, potentially through its SSRI-like properties. However, the molecular mechanisms underlying these effects and their health benefits for humans ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In addition to depression, CRYM/KR has been implicated in schizophrenia, Alzheimer's disease and amyotrophic lateral sclerosis 80 , possibly through the generation of reactive oxygen species 81 . Interestingly, we recently reported that the circulating human metabolites produced following saffron intake were able to protect human neurons against oxidative-stress-induced neurotoxicity by preserving cell viability in an ex vivo clinical model 27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to depression, CRYM/KR has been implicated in schizophrenia, Alzheimer's disease and amyotrophic lateral sclerosis 80 , possibly through the generation of reactive oxygen species 81 . Interestingly, we recently reported that the circulating human metabolites produced following saffron intake were able to protect human neurons against oxidative-stress-induced neurotoxicity by preserving cell viability in an ex vivo clinical model 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A close/delicate relationship exists between diet and gut microbiota composition, dysfunction of which is increasingly associated with mental illnesses. Saffron, obtained from the dried stigmas of Crocus sativus 21 has been reported to have anti-anxiety and anti-depressant properties as determined by us and others in both preclinical [22][23][24] and clinical trials [25][26][27] . Regarded as safe/well-tolerated, the effectiveness of saffron in the treatment of both anxiety and depression appears comparable to that of pharmaceutical intervention.…”
Section: Treatment Of Anxiety and Depression Has Predominantly Centre...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, oxidative stress (OS) is a major aetiopathological agent of MDD. 9 Most biochemical processes in biological organisms are mediated by redox reactions, in which electrons are transferred from a reducing agent to an oxidizing or oxidant agent. 10 Oxidants, also known as free radicals, are products permanently produced in the mitochondria due to cellular respiration, but they also occur in other organelles during their metabolic activities.…”
Section: Introductionmentioning
confidence: 99%